PENGARUH PENGGUNAAN E-COMMERCE, JUMLAH PELANGGAN, DAN MODAL USAHA TERHADAP PENDAPATAN PELAKU UMKM BIDANG KULINER - Dewi, Ida Ayu Prasista Praba; Indrajaya, I Gusti Bagus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
MSMEs, especially the culinary sector, were one of the sectors that were severely affected during the Covid-19 pandemic, which was marked by a decrease in income due to a decrease in people's purchasing power and policies to limit community activities. So we need a study that looks at what factors affect the income of MSMEs in the culinary field to anticipate a deeper decline in income. The use of E-commerce, the number of customers, and business capital are important factors that can affect the income of MSMEs in the culinary sector during the Covid-19 pandemic. Therefore, the purpose of this study is to analyze the effect of simultaneous and partial use of E-commerce, number of customers, and business capital on the income of SMEs in the culinary sector in West Denpasar. This study uses an associative quantitative approach. The analysis technique in this study uses multiple linear regression analysis techniques. The results of this study found that the variables of the use of E-commerce, the number of customers, and business capital simultaneously had a significant effect on the income of MSME actors in the culinary field in West Denpasar. Partially, the variables of the use of E-commerce, the number of customers, and business capital have a positive and significant effect on the income of MSME actors in the culinary field in West Denpasar.